2020
DOI: 10.18488/journal.aefr.2020.105.547.558
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Free Cash Flows on Dividend Pay-Out in Jordanian Banks

Abstract: Dividend pay-out is a concern for both managers and shareholders. The managers may use dividend policy to signal their performance. Thus, this study examines the effect of free cash flow, liquidity, bank size, leverage, profitability and bank age on the dividend pay-out ratio. The multiple regression analysis (panel data) was used to examine the hypothesis. The study found that free cash flow, liquidity, leverage and profitability were influential factors affecting the dividend pay-out ratio in Jordanian banks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…[3] stated that dividend policy was influenced by bank size, profitability, capital adequacy, credit risk but liquidity had no effect on dividend policy, [4] proved debt policy, returns on assets (ROA), company size and SEABC free cash flow influenced dividend policy. [5] also found that free cash flow, liquidity, leverage and profitability were influential factors affecting the dividend payout ratio. [6] presented research results which proved a significant positive effect of profitability on dividend policy but leverage and firm size had a negative relationship with dividend policy decision making.…”
Section: Introductionmentioning
confidence: 92%
“…[3] stated that dividend policy was influenced by bank size, profitability, capital adequacy, credit risk but liquidity had no effect on dividend policy, [4] proved debt policy, returns on assets (ROA), company size and SEABC free cash flow influenced dividend policy. [5] also found that free cash flow, liquidity, leverage and profitability were influential factors affecting the dividend payout ratio. [6] presented research results which proved a significant positive effect of profitability on dividend policy but leverage and firm size had a negative relationship with dividend policy decision making.…”
Section: Introductionmentioning
confidence: 92%
“…Kapasitas suatu bisnis untuk menghasilkan keuntungan sambil memanfaatkan sumber dayanya dikenal sebagai profitabilitas, dan rasio profitabilitas dapat digunakan untuk mengukur kemampuan ini. Sejumlah penelitian memperlihatkan bahwa profitabilitas memiliki dampak menguntungkan yang kuat terhadap kebijakan dividen, termasuk yang dilakukan Dang et al (2018), Al-Fasfus (2020, Angelia & Toni (2020), dan Sanjaya dkk. (2018).…”
Section: Pendahuluanunclassified
“…Meanwhile, the capital structure (leverage) literature begins with the phenomenal work created by Modigliani and Miller [7] about the irrelevance of capital structures continues to be an interesting topic in financial economics and has resulted in a great deal of research. However, previous studies have shown inconsistent results (see Pembayun and Subarjo [8], Ali et al [9], Hadistira et al [10], Al-Fasfus [11]).…”
Section: Introductionmentioning
confidence: 97%